The Phytochemical Rhein Mediates M6A-Independent Suppression of Adipocyte Differentiation - Huang, Linyuan; Zhang, Jun; Zhu, Xinyun; Mi, Xue; Li, Qiujie; Gao, Jing; Zhou, Jianheng; Zhou, Jun; Liu, Xiao-Min (Frontiers in Nutrition, 2021)
Adipogenesis is mediated by the complex gene expression networks involving the posttranscriptional modifications. The natural compound rhein has been linked to the regulation of adipogenesis, but the underlying regulatory mechanisms remain elusive. Herein, we systematically analyzed the effects of rhein on adipogenesis at both the transcriptional and posttranscriptional levels. Rhein remarkably suppresses adipogenesis in the stage-specific and dose-dependent manners. Rhein has been identified to inhibit fat mass and obesity-associated (FTO) demethylase activity. Surprisingly, side-by-side comparison analysis revealed that the rhein treatment and Fto knockdown triggered the differential gene regulatory patterns, resulting in impaired adipocyte formation. Specifically, rhein treatment mildly altered the transcriptome with hundreds of genes dysregulated. N6-methyladenosine (m6A) methylome profile showed that, although the supply of rhein induced increased m6A levels on a small subset of messenger RNAs (mRNAs), few of them showed dramatic transcriptional response to this compound. Moreover, the specific rhein-responsive mRNAs, which are linked to mitotic pathway, are barely methylated or contain m6A peaks without dramatic response to rhein, suggesting separate regulation of global m6A pattern and adipogenesis mediated by rhein. Further identification of m6A-independent pathways revealed a positive regulator, receptor expressing-enhancing protein 3 (REEP3), in guidance of adipogenesis. Hence, this study provides the mechanistic view of the cellular actions of rhein in the modulation of adipogenesis and identifies a potential novel target for obesity therapeutic research.